Presidents above Parties? : Presidents in Central and Eastern Europe, Their Formal Competencies and Informal Power. - Hloušek, Vít (Masarykova univerzita, 2013)
There may be a certain discrepancy between formal and actual positions of presidents in Central and East European countries which are classified as parliamentary democracies or systems with semi-presidential features. The aim of the forthcoming book is to find out whether we can trace an increasing engagement of presidents in everyday politics. If so, the authors will try to find out the cause of their increasing engagement, how they it is manifested and whether it is caused by the president's personality or rather by a changing structure of political opportunities that provides presidents wit.